Overexpression of 14-3-3 proteins enhances cold tolerance and increases levels of stress-responsive proteins of Arabidopsis plants. (December 2019) - Visconti, Sabina; D'Ambrosio, Chiara; Fiorillo, Anna; Arena, Simona; Muzi, Carlo; Zottini, Michela; Aducci, Patrizia; Marra, Mauro; Scaloni, Andrea; Camoni, Lorenzo
Highlights: 14-3-3ε and ω isoforms differentially regulate the H + -ATPase. Overexpression of 14-3-3ε and ω increases cold tolerance in Arabidopsis plants. TMT-proteomics reveals stress-related proteins regulated by 14-3-3ε-overexpression. Abstract: 14-3-3 proteins are a family of conserved proteins present in eukaryotes as several isoforms, playing a regulatory role in many cellular and physiological processes. In plants, 14-3-3 proteins have been reported to be involved in the response to stress conditions, such as drought, salt and cold. In the present study, 14-3-3ε and 14-3-3ω isoforms, which were representative of ε and non-ε phylogenetic groups, were overexpressed in Arabidopsis thaliana plants; the effect of their overexpression was investigated on H + -ATPase activation and plant response to cold stress. Results demonstrated that H + -ATPase activity was increased in 14-3-3ω-overexpressing plants, whereas overexpression of both 14-3-3 isoforms brought about cold stress tolerance, which was evaluated through ion leakage, lipid peroxidation, osmolyte synthesis, and ROS production assays. A dedicated tandem mass tag (TMT)-based proteomic analysis demonstrated that different proteins involved in the plant response to cold or oxidative stress were over-represented in 14-3-3ε-overexpressing plants.